The Tension Between Buddhism and Science Within Contemporary Chinese Buddhists: A Case Study on the Religious Conversion Narrative Among Monastics in Larung Gar Buddhist Academy - Liu, Yingxu (Religions, 2024)
This article delves into the perception of monastics from Larung Gar Buddhist Academy of Western China concerning the intertwining relationship between Buddhism and science, along with the impact of this perception on their worldview and life trajectory. Many monastics at Larung Gar Buddhist Academy initially held a high regard for science, dismissing Buddhism as superstition. However, upon gaining a comprehensive understanding of Buddhism through various opportunities, they came to believe that certain tenets of Buddhism are compatible with science, even suggesting that Buddhism could address some of the methodological and epistemological limitations of science and offer solutions to some issues that science is unable to resolve. This ultimately led them to embrace Buddhism and renounce worldly life. This study employs a case study to investigate the understanding of the relationship between Buddhism and science amongst the general public in contemporary China, an area underexplored by previous scholarship that predominantly concentrated on the philosophical scrutiny of the apologetic discourses towards the reconciliation between Buddhism and science of influential Buddhist ascetics and lay practitioners. Also, this study endeavors to demonstrate that despite the ongoing secularization of contemporary Chinese Buddhism in the “public sphere”, within the “private sphere” of Chinese Buddhism, there remain individuals who are pursuing the religious, sacred, and transcendental dimensions of Buddhism.